INTERNATIONALIZATION OF HIGHER EDUCATION AS A SUBJECT OF RESEARCH BY UKRAINIAN COMPARATIVISTS - Snitovska, Olha (Mountain School of Ukrainian Carpaty, 2023)
Against the backdrop of increasing globalization in the early 21st century, national education systems and individual universities have encountered the phenomenon of internationalization. Consequently, alongside the imperative of globalization, the study of the integration processes of higher education has become an important direction, focusing on the process of its internationalization. The aim of the article is to conduct a subject-synthesized analysis of how the issue of internationalization of higher education is reflected in the research of Ukrainian comparativists from the second half of the 1990s to the first decade of the 21st century. It is identified that within Ukrainian pedagogical comparativism and other fields of knowledge, a crucial interpretation of internationalization of higher education has solidified as one of the most important features/characteristics/trends/factors of modern development and modernization of national higher education systems and individual universities. When attempting to study this phenomenon, we navigate through the intertwining narratives of foreign and Ukrainian researchers. To fulfill this task, a structured analysis of a collection of scientific sources on the specified problem is proposed, categorized into three blocks: scientific-theoretical (analysis of the concept of internationalization of higher education by Ukrainian authors and scientific approaches to its study); content-thematic (analysis of the main thematic and area-specific aspects of studying internationalization of higher education by Ukrainian authors); comparative-analytical (analysis of the Ukrainian discourse regarding the relationship between processes of globalization of higher education and internationalization of higher education). The conclusions indicate that the issue of internationalization of higher education has become the subject of active domestic scientific discourse. Its theoretical foundation consists of studies by Western scientists, primarily appearing in the years 1998-2003. Under their influence, Ukrainian science has established an understanding of this phenomenon as a complex, multifaceted, dynamic, and contradictory process that transforms under the rapidly changing socio-cultural conditions but retains a key characteristic – an international dimension.